Association of Neutrophil–Lymphocyte Ratio and the Presence of Neonatal Sepsis. (3rd December 2020) - Li, Tiewei; Dong, Geng; Zhang, Min; Xu, Zhe; Hu, Yidi; Xie, Bo; Wang, Yuewu; Xu, Bangli
Abstract : The neutrophil–lymphocyte ratio (NLR) is an emerging risk factor of sepsis that is receiving increasing attention. However, the relationship between NLR and the presence of sepsis in neonates is poorly studied. Here, we retrospectively recruited 1480 neonates and collected and analyzed relevant clinical and laboratory data. According to the International Pediatric Sepsis Consensus, 737 neonates were diagnosed with sepsis, and 555 neonates were suspected for having infection. Neonates with hyperbilirubinemia (n = 188 ) served as controls. Neonates with sepsis had significantly elevated neutrophil counts and NLR (P < 0.001 ). The proportion of neonates with sepsis increased significantly from 41.6% when NLR < 0.91 to 66.2% when NLR > 1.88 group (P < 0.001 ). Multiple logistic regression analysis showed that NLR was an independent risk factor for the presence of neonatal sepsis. Receiver operating characteristic (ROC) curve analysis showed that the optimal cut-off value NLR for predicting the presence of neonatal sepsis was 1.62 (area under curve AUC = 0.63, 95% CI 0.60–0.66, P < 0.001 ). In conclusion, our data suggest that elevated NLR levels are associated with a higher neonatal sepsis risk.